Characterization of left atrial geometry and function in patients with non-obstructive hypertrophic cardiomyopathy: a cardiac magnetic resonance imaging study. (14th October 2021) - Agoston Coldea, L; Muresan, I; Zlibut, A; Cojan-Minzat, B O; Cionca, C; Horvat, D
Abstract: Background: Left atrial (LA) function and geometry are important predictors of cardiac dysfunction and prognosis in cardiovascular disease, however studies that evaluate their role in patients with hypertrophic cardiomyopathy (HCM) are scarce. Furthermore, altered LA phasic functions might become predictors for disease progression, even in these patients. This study sought to assess the use of cardiac magnetic resonance imaging (CMR) in the assessment of LA function and geometry in patients with HCM. Methods: We conducted a prospective case-control study on eighty-six patients with first non-obstructive HCM (NO-HCM) diagnosis. They underwent standard cardiovascular examinations and CMR. LA geometry was assessed using LA maximum, minimum and pre-A volumes (LAVmax, LAVmin, LAVpre-A), LA sphericity index (LASI), and LA late gadolinium enhancement (LA-LGE). LA phasic functions were assessed using LA total emptying fraction (LATF), LA passive emptying fraction (LAPF) and LA active emptying fraction (LAAF). LA strain parameters of all three phasic functions were quantified by total strain (et); passive strain (ep), active strain (ea). Results: 86 HCM patients (51±13.7) and 86 healthy volunteers (51±13.6) were enrolled. LA volumes parameters were significantly increased in NO-HCM group (LAVmax: 39.7 vs 33.9 mL/m 2 ; LAVmin: 20.4 vs 13.9 mL/m 2 ; LAVpre-A31.7 vs 24.1 mL/m 2, all p<0.001). LA geometry was significantly altered by an increased LASI (56.3 vs 39.7, p<0.001). All three LA phasic functions and strain were impaired in those withHCM (LATF: 49.2±6.5% vs. 58.8±3.1%, et 30.9% vs 39.8%; LAPF: 19.9±5.9% vs. 29.1±8.4%, ep 15.9% vs 18.1%; LAAF: 36.3±8.8% vs. 41.2±8.2%, ea: 20.5% vs 29.1%; all p<0.001). Last but not least, LA replacement fibrosis was present in 39.5% (n=34) of patients with NO-HCM. In multivariable analysis, increased LA-LGE was associated with lower LAPF, peak global longitudinal LA strain (p<0.001). Conclusion: LA function, strain and geometry are significantly impaired in patients with NO-HCM, even before left ventricular outflow tract obstruction occurs. These parameters might have predictive ability, however further studies are required. Funding Acknowledgement: Type of funding sources: None.